2017
DOI: 10.1038/ismej.2017.143
|View full text |Cite
|
Sign up to set email alerts
|

DNA-SIP based genome-centric metagenomics identifies key long-chain fatty acid-degrading populations in anaerobic digesters with different feeding frequencies

Abstract: Fats, oils and greases (FOG) are energy-dense wastes that can be added to anaerobic digesters to substantially increase biomethane recovery via their conversion through long-chain fatty acids (LCFAs). However, a better understanding of the ecophysiology of syntrophic LCFA-degrading microbial communities in anaerobic digesters is needed to develop operating strategies that mitigate inhibitory LCFA accumulation from FOG. In this research, DNA stable isotope probing (SIP) was coupled with metagenomic sequencing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 67 publications
3
68
0
Order By: Relevance
“…The high representation of syntrophs and methanogens in the co‐occurrence network may also be attributed to their metabolic specialization (Sieber et al ., ), suggesting that their ecological niches are not easily filled by other taxa (Werner et al ., ). Yet, recent work has shown high strain variability within digester syntrophic communities under different feeding strategies (Ziels et al ., , ), indicating that selective forces may still govern the syntrophic community structure in different digester environments.…”
Section: Resultsmentioning
confidence: 99%
“…The high representation of syntrophs and methanogens in the co‐occurrence network may also be attributed to their metabolic specialization (Sieber et al ., ), suggesting that their ecological niches are not easily filled by other taxa (Werner et al ., ). Yet, recent work has shown high strain variability within digester syntrophic communities under different feeding strategies (Ziels et al ., , ), indicating that selective forces may still govern the syntrophic community structure in different digester environments.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, two 13 C-enriched OTUs in both digesters were assigned to Methanothrix (formerly Methanosaeta ), which likely scavenge the 13 C-acetate generated by Syntrophomonas during 13 C-butyrate degradation. While one previous study observed that Syntrophaceae was predominantly enriched in anaerobic digester granular sludge incubated with 13 C-labeled butyrate (10), various other studies also detected Syntrophomonadaceae populations as active syntrophic butyrate degraders in anaerobic digester sludge using 14 C-labeled butyrate and MAR-FISH (15), in anaerobic digester sludge through SIP using 13 C-labeled oleate (12), and in rice paddy soil with SIP using 13 C-labeled butyrate (16). In the latter two studies, acetate-scavenging partners ( Methanothrix and Methanosarcinaceae ) were also enriched.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated the potential of combining DNA-stable isotope probing (SIP) with genome-resolved metagenomics to identify syntrophic populations degrading the long-chain fatty acid, oleate (C 18:1 ), within anaerobic digesters (12). Stable-isotope informed metagenomic sequencing can enrich metagenomic libraries with genomic sequences of actively-growing microbes that incorporate 13 C into their biomass from an added labeled substrate (13), and thus allows for a ‘zoomed in’ genomic view of low-abundance populations such as syntrophs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations